2021
DOI: 10.21203/rs.3.rs-313477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of New Intragenic HBB Haplotypes Model for the Prediction of Beta-Thalassemia in the Malaysian Population

Abstract: This study sought to determine the potential role of HBB haplotypes for the prediction of beta-thalassemia in the Malaysian population. A total of 543 archived samples were reviewed and selected for this study. Five tagging SNPs in the beta-globin gene (HBB; NG_000007.3) were recorded and analysed for SNP-based and haplotype association using SHEsis online software. Single-SNP-based association analysis showed three tagging SNPs have statistical significant association with beta-thalassemia; IVS2-16G>C (p=0… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Hemoglobin A (HbA) is the most dominant type of hemoglobin found in healthy adults and is made up of two α-and two β-globin chains (50,51). The normal synthesis of β-globin chains was found to be reduced in HbE/β-thalassemia patients (2,52). Similarly, the results from the present study showed lower HbA levels in HbE/β-thalassemia patients compared to the reference values.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Hemoglobin A (HbA) is the most dominant type of hemoglobin found in healthy adults and is made up of two α-and two β-globin chains (50,51). The normal synthesis of β-globin chains was found to be reduced in HbE/β-thalassemia patients (2,52). Similarly, the results from the present study showed lower HbA levels in HbE/β-thalassemia patients compared to the reference values.…”
Section: Discussionsupporting
confidence: 67%
“…Thalassemia is an inherited disease associated with reduced synthesis of one or more globin chains and resulting in a defective hemoglobin (Hb) production and earlier damage to red blood cells (1,2). Hemoglobin E (HbE)/β-thalassemia is the most common severe thalassemia in South and Southeast Asian countries (3).…”
Section: Introductionmentioning
confidence: 99%